A Blend of Phellodendron and Crape Myrtle Improves Glucose Tolerance in Exercise-Trained Men - Canale, Robert E. (Libertas Academica, 2011)
BACKGROUND: The purpose of this study was to investigate the acute effects of a nutritional supplement containing a proprietary blend of Phellodendron and Crape Myrtle on serum glucose and insulin in response to a modified oral glucose tolerance test (OGTT). METHODS: Using a randomized, double-blind, cross-over design, 10 exercise-trained, non-diabetic men reported to the lab in a 10 hour fasted state, on two different mornings separated by 1–2 weeks, and were subjected to an OGTT by ingesting a 75 gram dextrose solution. Fifteen minutes prior to the OGTT subjects ingested either a dietary supplement containing a blend of Phellodendron and Crape Myrtle (SUPP) or a placebo (PLA). Blood samples were collected before ingestion of the SUPP or PLA and at 15, 30, 45, 60, and 75 minutes post-ingestion of the dextrose load. Samples were analyzed for serum glucose and insulin. RESULTS: In relation to serum glucose, a condition effect was noted (P = 0.01), with values lower for SUPP compared to PLA. In relation to serum insulin, a trend for a condition effect was noted (P = 0.06), with values lower for SUPP compared to PLA. CONCLUSION: These findings indicate that acute ingestion of a dietary supplement containing a blend of Phellodendron and Crape Myrtle can lower the serum glucose response to a modified OGTT, while resulting in a non-significant attenuation in insulin response. These data are specific to a small sample of exercise-trained, non-diabetic men.